Emergence of Rapid Oxygen Surface Exchange Kinetics during in Situ Crystallization of Mixed Conducting Thin Film Oxides - Chen, Ting; Harrington, George F; Masood, Juveria; Sasaki, Kazunari; Perry, Nicola H (ACS applied materials & interfaces, 2019)
The oxygen surface exchange kinetics of mixed ionic and electronic conducting oxides (MIECs) play a critical role in the efficiency of intermediate-to-high-temperature electrochemical devices. Although there is increasing interest in low-temperature preparation of MIEC thin films, the impact of the resultant varied degrees of crystallinity on the surface exchange kinetics has not been widely investigated. Here, we probe the effect of crystallization on oxygen surface exchange kinetics in situ, by applying an optical transmission relaxation (OTR) approach during annealing of amorphous films. OTR enables contact-free, in situ, and continuous quantification of the oxygen surface exchange coefficient (k chem); we previously applied it to Pr x Ce1–x O2−δ and SrTi1–x Fe x O3−δ thin films. In this work, the OTR approach was successfully extended to other mixed conducting thin film compositions for the first time (i.e., perovskite SrTi0.65Co0.35O3−δ and Ruddlesden–Popper Sr2Ti0.65Fe0.35O4±δ), as well as to Pr0.1Ce0.9O2−δ, enabling quantification of the k chem of their native surfaces and comparison of the behavior of films with different final crystal structures. All thin films were prepared by pulsed laser deposition at 25 or 700–800 °C and subject to subsequent thermal treatments with simultaneous OTR monitoring of k chem. The surface roughness, grain size, and crystallinity were evaluated by scanning probe microscopy, X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. Fluorite Pr0.1Ce0.9O2−δ films grown at 25 °C did not exhibit an increase in k chem after annealing, as they were already crystalline as grown at 25 °C. For all other compositions, OTR enabled in situ observation of both the crystallization process and the emergence of rapid surface exchange kinetics immediately upon crystallization. Perovskite SrTi0.65Co0.35O3‑δ and Ruddlesden–Popper Sr2Ti0.65Fe0.35O4±δ thin films grown at 25 °C exhibited at least 1–2 orders of magnitude enhanced k chem after annealing compared with highly crystalline thin films grown at 800 °C, indicating the benefits of in situ crystallization.